2018
DOI: 10.1111/gcb.14481
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impact and adaptation for wheat protein

Abstract: Nendel 38 | Jørgen Eivind Olesen 37 | Taru Palosuo 44 | John R. Porter 42,45,46 | Eckart Priesack 39 | Dominique Ripoche 47 | Mikhail A. Semenov 48 | Claudio Stöckle 17 | Pierre Stratonovitch 48 | Thilo Streck 33 | Iwan Supit 49 | Fulu Tao 50,44 | Marijn Van der Velde 51 | Daniel Wallach 52 | Enli Wang 53 | Heidi Webber 30,38 AbstractWheat grain protein concentration is an important determinant of wheat quality for human nutrition that is often overlooked in efforts to improve crop production. We tested and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
230
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 397 publications
(239 citation statements)
references
References 68 publications
4
230
1
4
Order By: Relevance
“…All models in the ensemble were calibrated for the phenology of local cultivars and used site‐specific soils and crop management. The multi‐model ensemble used here has been tested against observed field data and showed reliable response to changing climate in several previous studies, including responses of model ensemble to elevated CO 2 , post‐anthesis chronic warming and different heat shock treatments during grain filling (Asseng et al, ; Wallach et al, ). Hoffman et al () and Ruane et al () showed that a multi‐model ensemble can also reproduce some of observed seasonal yield variability.…”
Section: Methodsmentioning
confidence: 92%
See 4 more Smart Citations
“…All models in the ensemble were calibrated for the phenology of local cultivars and used site‐specific soils and crop management. The multi‐model ensemble used here has been tested against observed field data and showed reliable response to changing climate in several previous studies, including responses of model ensemble to elevated CO 2 , post‐anthesis chronic warming and different heat shock treatments during grain filling (Asseng et al, ; Wallach et al, ). Hoffman et al () and Ruane et al () showed that a multi‐model ensemble can also reproduce some of observed seasonal yield variability.…”
Section: Methodsmentioning
confidence: 92%
“…An ensemble of 31 wheat crop models was used to assess climate change impacts for 60 representative wheat‐growing locations developed by the AgMIP‐Wheat team (Assenget al, ; Wallach et al, ). All models in the ensemble were calibrated for the phenology of local cultivars and used site‐specific soils and crop management.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations